Comorbidities and neurosurgical interventions in a cohort with connective tissue disorders - Ilene S. Ruhoy; Paolo A. Bolognese; Jared S. Rosenblum; Randall A. Dass; Navdeep S. Nayyer; Navdeep S. Nayyer; Jeffrey D. Wood; Jeffrey D. Wood; John B. Biggins; John B. Biggins (Frontiers in Neurology)
BackgroundConnective tissue disorders (CTDs) are a heterogeneous group of disorders often presenting with a variety of comorbidities including musculoskeletal, autonomic, and immune dysfunction. Some CTDs such as hypermobile Ehlers-Danlos syndrome (hEDS), which is one of the most common, have been associated with neurological disorders requiring surgical intervention. The frequency of these comorbidities in these populations and their subsequent requirement for neurosurgical intervention remains unclear.MethodsBased on our initial experience with this population, we investigated the presentation rates of specific comorbidities and neurosurgical interventions in a cohort of individuals referred to our institution for evaluation and neurosurgical management of issues secondary to diagnosed or suspected CTDs from 2014 to 2023. Primary diagnoses were made by referring physicians or institutions based on clinical presentation and standard-of-care criteria. We evaluated relationships between diagnoses and surgical interventions by multivariate correlation and intersection plots using the UpSetR package.ResultsOf 759 individuals, we excluded 42 based on incomplete data. From the remaining (total cohort, N = 717), 460 (64%) individuals were diagnosed with hEDS, 7 were diagnosed with a CTD other than hEDS, and 250 lacked a formal CTD diagnosis. We found that individuals with hEDS had a higher frequency of certain comorbidities, such as Mast Cell Activation Disorder and Postural Orthostatic Tachycardia Syndrome, and neurosurgical intervention compared to individuals without a CTD diagnosis (unaffected). Of the total cohort, 426 (59%) were diagnosed with Chiari I Malformation, which shared a significant overlap with hEDS. Of those who elected to undergo surgery (n = 612), 61% required craniocervical fusion (CCF). Notably, of the 460 individuals diagnosed with hEDS, 404 chose surgical intervention, of which, 73% required CCF for craniocervical instability.ConclusionIn this retrospective study of individuals referred to our institution for evaluation of CTDs potentially requiring neurosurgical intervention, we defined the frequency of presentation of specific comorbidities that we commonly encountered and revealed the rate at which they required neurosurgical intervention.